Inovasi Material Kendali Neutron untuk Small Modular Reactor (SMR): Kajian Literatur Sistematis Boron, Hafnium, dan Kompositnya - Febrian Ainun Rahman; Sovian Aritonang (Fakultas Teknik UMSU, 2026)
The development of Small Modular Reactor (SMR) technology demands innovative neutron absorber materials that are efficient, thermomechanically stable, and resistant to long-term irradiation. Boron carbide (B₄C) exhibits a high thermal neutron absorption cross-section, while hafnium (Hf) offers superior structural stability and does not generate helium gas; however, studies integrating both materials remain limited. The main research gap lies in the lack of a comprehensive analysis comparing and combining the neutronic and thermomechanical characteristics of B–Hf materials for SMR control systems. This study aims to conduct a systematic literature review on neutron absorber materials based on boron, hafnium, and their composites to identify key parameters affecting neutron absorption efficiency, thermal stability, and irradiation resistance. Using the Systematic Literature Review (SLR) method applied to 15 Scopus-indexed journals from 2019–2024, the results indicate that Hf–B₄C composites provide an optimal balance between neutron absorption efficiency (≥90%), thermal conductivity (28–35 W·m⁻¹·K⁻¹), and structural stability up to 900 °C, making them a promising candidate for adaptive neutron control systems in next-generation SMRs.